Comparing young people's experience of technology-delivered v. face-to-face mindfulness and relaxation: Two-armed qualitative focus group study. (April 2017) - Tunney, Conall; Cooney, Patricia; Coyle, David; O'Reilly, Gary
Abstract : Background: The current popularity of mindfulness-based practices has coincided with the increase in access to mobile technology. This has led to many mindfulness apps and programs becoming available, some specifically for children. However, little is known about the experience of engaging with mindfulness through these mediums. Aims: To explore children's experience of mindfulness delivered both face-to-face and through a computer game to highlight any differences or similarities. Method: A two-armed qualitative focus groups design was used to explore children's experiences. The first arm offered mindfulness exercises in a traditional face-to-face setting with guided meditations. The second arm offered mindfulness exercises through a computer game avatar. Results: Themes of relaxation, engagement, awareness, thinking, practice and directing attention emerged from both arms of focus groups. Subthematic codes highlight key differences as well as similarities in the experience of mindfulness. Conclusions: These results indicate that mindfulness delivered via technology can offer a rich experience.